Development of E-Student Worksheet Based on Problem-Based Learning Model Using Liveworksheet Platform to Improve Students' Critical Thinking Skills (Jurnal Pendidikan Fisika, 2025)
Physics education in the 21st century must be directed toward developing higher-order and process-oriented skills that enable students to think critically and engage in scientific inquiry. Traditional instructional practices often emphasize memorization, leaving limited opportunities for students to cultivate critical thinking skills (CTS) and science process skills (SPS), particularly in abstract topics such as sound waves. This research was conducted to develop and evaluate a problem-based learning (PBL) model assisted by live worksheets to enhance students’ CTS and SPS. The study employed a research and development design based on the ADDIE model, which consisted of the stages of analysis, design, development, implementation, and evaluation. Thirty-five grade XI students at a public senior high school in Makassar participated in the implementation. Data were obtained through expert validation, a CTS test, SPS observation sheets, and student response questionnaires. Expert validation results indicated that the product was in the very valid category, with average scores above 85%, while student responses placed the worksheets in the practical category, with averages exceeding 80%. Statistical analysis of CTS using pretest-posttest measures showed significant improvement, with normalized gain (N-Gain) scores categorized as medium. Observations further confirmed that students’ SPS, such as hypothesizing, experimenting, and interpreting results, improved substantially during the learning process. The novelty of this study lies in positioning live worksheets as a central scaffold within PBL cycles, directly guiding inquiry and reasoning rather than serving as supplementary material. The findings conclude that the developed PBL-assisted live worksheets are valid, practical, and effective, contributing to advances in physics education by strengthening both critical thinking and science process skills.
Keywords: critical thinking skills; liveworksheets platform; physics education; problem-based learning; sound waves